New Evidence on Cyclical Variation in Average Labor Costs in the United States - Gu, Grace Weishi; Prasad, Eswar; Moehrle, Thomas (The Review of Economics and Statistics, 2020)
We provide new evidence on the cyclicality of employers' real labor costs using BLS establishment job data for the 1982–2018 period. Average straight-time wages have become countercyclical since the financial crisis and the subsequent Great Recession. So have benefit expenditures and overall labor costs, as well as major benefit expenditures, including health insurance and Social Security. Consistent with prior literature, we find that total earnings—the sum of straight-time wages, bonuses, and overtime earnings—were procyclical before 2008; even earnings have become countercyclical since then. The increasing countercyclicality of labor costs is largely attributable to periods with below-trend GDP.